2001
DOI: 10.1128/iai.69.6.4141-4145.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenicity and Cytokine-Inducing Properties ofStreptococcus pyogenesSuperantigens: Comparative Study of Streptococcal Mitogenic Exotoxin Z and Pyrogenic Exotoxin A

Abstract: Streptococcal mitogenic exotoxin Z (SMEZ), a superantigen derived from Streptococcus pyogenes, provoked expansion of human lymphocytes expressing the V␤ 2, 4, 7 and 8 motifs of T-cell receptor. SMEZ was pyrogenic in rabbits and stimulated the expression of the T-cell activation markers CD69 and cutaneous lymphocyteassociated antigen. A variety of cytokines was released by human mononuclear leukocytes stimulated with SMEZ, which was 10-fold more active than streptococcal pyrogenic exotoxin A. Th2-derived cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…This may be because SMEZ is the only significant stimulus present in supernatant which can lead to cytokine production, or, more likely, because SMEZ is an essential cofactor which synergizes with other streptococcal proteins. Very recently, it was reported that a native preparation of the SMEZ-16 allele was 10-fold more active than a native preparation of SPEA when cytokine production from human mononuclear cells was quantified (20). The cytokine-stimulating role of a range of streptococcal secreted proteins has been extensively reported (21,22); data from the current study underpin the value of examining protein function in a physiological context, using supernatants from isogenic strains which are free of endotoxin contamination.…”
Section: Discussionmentioning
confidence: 68%
“…This may be because SMEZ is the only significant stimulus present in supernatant which can lead to cytokine production, or, more likely, because SMEZ is an essential cofactor which synergizes with other streptococcal proteins. Very recently, it was reported that a native preparation of the SMEZ-16 allele was 10-fold more active than a native preparation of SPEA when cytokine production from human mononuclear cells was quantified (20). The cytokine-stimulating role of a range of streptococcal secreted proteins has been extensively reported (21,22); data from the current study underpin the value of examining protein function in a physiological context, using supernatants from isogenic strains which are free of endotoxin contamination.…”
Section: Discussionmentioning
confidence: 68%
“…The smeZ transcript level was 24 times higher than the speA2 level ( Fig. 8 C and D), a very important finding given that SmeZ has been reported to be at least 10 times more potent than other GAS PTSAgs in the ability to stimulate cytokine release by human T cells (29). Together, the data suggest that these three PTSAgs act sequentially to assist colonization, with speJ contributing early when GAS densities are low and smeZ and speA2 contributing preferentially to a rapid increase in CFUs.…”
Section: Pyrogenic Toxin Superantigens (Ptsags)mentioning
confidence: 83%
“…Recognition of PAMP by the involved host cells, primarily neutrophils, monocytes and dendritic cells, leads to pro-inflammatory responses, including the release of cytokines, chemokines and other mediators, which are required for an effective host response (Medzhitov and Janeway, 1997); however, a range of other molecules from bacteria also has the capacity to induce cytokine production (Henderson et al, 1996). Streptococci have several functional proteins which are involved in the host proinflammatory response, such as pneumolysin of S. pneumoniae (Houldsworth et al, 1994;Rogers et al, 2003;Thornton and McDaniel, 2005), mitogenic exotoxin Z, pyrogenic exotoxin A and M protein of S. pyogenes (Muller-Alouf et al 2001;Pahlman et al, 2006), and antigen I/II of S. mutans (Soell et al, 1994) and other streptococci (Chatenay-Rivauday et al, 2000). This study is the first report showing that the histone-like DNA binding protein of S. intermedius (Si-HLP), a highly conserved structural protein within streptococci, is a potent activator upregulating pro-inflammatory cytokines in human monocytes.…”
Section: Discussionmentioning
confidence: 99%